Homeless people's transition from the hidden world of socialism to the quasi-welfare social safety of contemporary Hungary evidence from Szeged - Nagy Terézia (Belvedere Meridionale Szeged, 2015)
In Hungary, homelessness has reappeared in the 1990s as a kind of social problem and also as a phenomenon. Th e intention of this study is to show how homelessness has become visible to society and why the problem was perceived so late, despite the fact that homeless people were part of the socialist society, even if in a latent way. Fieldwork was carried out in Szeged, a city in southern Hungary aft er 2002. During the research, I have participated in the everyday lives of homeless groups as an observer; I have conducted interviews and examined the social networks, problems and possibilities of the homeless. In this study, I show that the Hungarian circumstances, politics and structural changes were diff erent from their Western counterparts, since Hungary took a diff erent path. Th is trajectory infl uences the fate of those who become homeless. Even so, twenty years aft er the end of socialism, a number of parallels with the West, and with the United States in particular, can be discerned.
Keywords: Társadalomtudományok; Szociológia; Bölcsészettudományok; Történettudomány és régészet